Ring-necked pheasant survival, nest habitat use, and predator occupancy in Kansas spring cover crops - Annis, Adela C. (Kansas State University, 2019)
The ring-necked pheasant (Phasianus colchicus) is a popular and economically important upland gamebird in Kansas. Population declines have stakeholders seeking methods to manage populations on agricultural lands. Cover crops planted during the breeding period may provide important resources pheasants require for survival and successful reproduction. I evaluated three cover crop mixes; a custom mix, commercial mix, a wildlife mix, and a chemical fallow control in three counties in western Kansas, during 2017 and 2018 to determine their potential as a management practice for increasing pheasant habitat. I tested the relative effects of spring cover crops on female pheasant survival, nest survival, nest-site selection, and mesocarnivore occupancy. Females pheasants (73) were captured via nightlighting during February – April and fitted with 15-g very-high-frequency radio collars and monitored by telemetry. I placed 58 camera traps on field edges and within cover crop treatments from April to September. Vegetation data were collected at nests and random points to assess nest-site selection and weekly random vegetation points were sampled within treatments. I used known fate and nest survival models in the package RMark interface in R to investigate adult and nest survival (R Core Team 2018). Adult breeding season survival was 0.57 (SE < 0.0001, CI = 0.5739 – 0.5740). Percent spring cover crop positively influenced adult survival (AICc wi = 0.450). Nest survival was 0.36 (SE < 0.001, CI = 0.3614 - 0.3614). Daily nest survival followed a pattern of high survival that gradually declined over the breeding season. Resource selection functions suggest female ring-necked pheasants selected vegetation between 5-7 dm at 50% VOR for nest sites (AICc wi = 0.97). Chi-square analyses suggest females selected Conservation Reserve Program (CRP) patches for nest sites more than expected during both years (2017 χ²₄ = 26.49, P < 0.001; 2018 χ²₄ = 9.80, P = 0.04). CRP supported 57% of nests and 56% of successful nests relative to other cover types. All three of the monitored nests in cover crops were depredated. Ring-necked pheasant occupancy was greatest on edges of treatments (ψ = 0.97, SE = 0.081) and influenced by proportion of the Chick Magnet seed mix (AICc wi = 0.68). Mesocarnivore occupancy was greatest on treatment edges with a constant occupancy of 0.99 (SE = 0.47, AICc wi = 0.66). Spring cover crops provide cover and foraging resources when the majority of agricultural practices are fallow. Spring cover crops do not provide sufficient vertical cover for nesting until after peak nesting occurs, especially during cooler than average winter and spring conditions such as 2018. However, there are tangible benefits of spring cover crops to other biological periods, such as adult female survival, and brood resources if placement of cover crops is targeted near quality nest habitat. My results indicates wheat is an ecological trap for nesting due to increased predation and destruction during harvest. Providing quality nest structure will reduce females nesting in wheat. Incorporation of spring cover crops is a beneficial wildlife management tool that can increase ring-necked pheasant habitat on the landscape.
Keywords: Phasianus colchicus; Ring-necked pheasant; Cover crop; Survival; Nest-site selection; Predator Occupancy